P-011 Mri selected isolated m2 occlusion elvo patients show improvement in aphasia after thrombectomy at extended time lsw. (23rd July 2017) - Cristiano, B; Cicilioni, K; Pond, M; Lee, J; Promod, P; Oyoyo, U; Jacobson, J
Abstract : Background: Isolated occlusion of the MCA M2 segment may result in significant motor or speech symptoms and is often amenable to mechanical thrombectomy. Although isolated M2 occlusions are not uncommon they are unrepresented in recent large randomized controlled trials, and therefore, represent a population of great interest. Here we show significant response to therapy among a cohort of M2 occlusion patients, many treated at extended time LSW after MRI assessment. Population: ELVO patients with isolated occlusion of the right or left MCA M2 segment, baseline NIHSS speech score ≥1, baseline mRS ≤2, age ≥18, and no MRI contraindication. Methods: Retrospective cohort analysis with primary outcome discharge NIHSS speech score and secondary outcome NIHSS speech score improvement. Results: From an institutional stroke intervention dataset representing n=80 ELVO patients treated with thrombectomy between 12/25/2014 and 8/14/2016, n=8 cases were identified meeting inclusion criteria. Median age was 66, median baseline NIHSS was 9 (range: 6–21), and mean CT ASPECTS was 9.25. 3/8 (37.5%) received IV tPA, median time LSW to femoral access was 216 min (IQR: 330–534), and median baseline DWI volume was 6 mL (IQR: 5–18). 7/8 patients studied (87.5%) showed at least one-point improvement in NIHSS speech score at discharge with 6/8 (75%) either insignificant or mild aphasia at discharge. 2/8 patients had time to femoral access ≤6 hour LSW, both had mild aphasia that was resolved at discharge. 4/5 patients presenting beyond 6 hour LSW had insignificant or mild aphasia at discharge, a response rate of 80% and not statistically different from the early presenting group (OR: 1.5 [95CI: 0.82–2.64]). Conclusion: MRI selected ELVO patients with isolated M2 occlusion and significant aphasia represented in this cohort showed excellent response to therapy at extended time LSW. Disclosures: B. Cristiano: None. K. Cicilioni: None. M. Pond: None. J. Lee: None. P. Promod: None. U. Oyoyo: None. J. Jacobson: None.